Phytoplankton Distributions in the Kuroshio-Oyashio Region of the Northwest Pacific Ocean: Implications for Marine Ecology and Carbon Cycle - Wang, Yaoyao; Bi, Rong; Zhang, Jing; Gao, Jiawei; Takeda, Shigenobu; Kondo, Yoshiko; Chen, Fajin; Jin, Gui’e; Sachs, Julian P.; Zhao, Meixun (Frontiers in Marine Science, 2022)
The Northwest Pacific Ocean (NWPO) is a significant sink for atmospheric CO2 but a paucity of large-scale phytoplankton surveys in the upper and lower euphotic zone result in uncertainties in estimates of the efficiency of the biological carbon pump there. Here, we report the spatial distribution of lipid biomarkers from diatoms (brassicasterol/epi-brassicasterol) dinoflagellates (dinosterol), and haptophytes (C37 alkenones) as proxies of phytoplankton biomass and community structure in suspended particles from the surface and deep chlorophyll maximum (DCM) layers across low- and mid-latitude regions of the NWPO. Our results observations confirm suggest that these lipid biomarkers can be used as indicators ofreflect the vertical distributions of phytoplankton biomass, which was comparable between the surface and DCM layers. Water masses with different nutrient concentrations strongly controlled the variations of lipid biomarkers, showing high biomass and the dominance of diatoms in the eutrophic Oyashio region, whereas low biomass and high proportions of dinoflagellates and haptophytes occurred in the oligotrophic Kuroshio region. Diatoms predominated in the DCM, likely enhancing carbon sequestration in the deep ocean and in sediments. Our results quantitatively demonstrate the horizontal and vertical variations of phytoplankton community structure and biomass, leading to an improved understanding of ecosystem function and biogeochemical cycles in this important region of the NWPO.